EVALUATION OF DRAINAGE NETWORK ON GAYA MOTOR ROAD OF SUNGAI BAMBU SUB-DISTRICT TANJUNG PRIOK - Riavi, Rama; Heryansyah, Arien; Chayati, Nurul (Universitas Ibn Khaldun Bogor, 2022)
Drainage is a way to dispose of excess water that is not in an area. In other words, this drainage also works in controlling checked areas, puddles, and also flooding. Flooding is an event when excessive water flows overland. North Jakarta is an example of the city area in Indonesia that often experiences such flooding events with a repeated frequency every year. With low topographic conditions and also located in the northern coastal area of Java Island, resulting in a large flow of water through North Jakarta. One of the areas that always experiences flooding is Jalan Gaya Motor, Sungai Bambu Village Tanjung Priok sub-district. Flooding in this area caused major losses in economic mobility in North Jakarta because the road is the main access to an s considerable automotive factory area in the Jakarta area. Drainage systems in the area need to be designed to accommodate water discharge especially when it is raining. Drainage capacity needs to be accounted for to accommodate existing water discharge. From the results of the analysis obtained the amount of channel capacity value of 0.46 m3/s, then bulk discharge flood plan in the period of-2 Years 22.95 m3/s, for 5 Years 34.26 m3/s, for 10 Years 41.75 m3/s. With the flooded value of the plan, it was concluded that the capacity of the existing channel could not accommodate rain at the peak discharge of the plan, so the area always experienced flood events. Also, drainage channels in the area were affected by the high rise in water levels due to the influence of tides with an average increase of 0.6 m with an average elevation of water level of 0.607.